Adverse effects of COVID-19 mRNA vaccines: the spike hypothesis. Issue 7 (July 2022) - Trougakos, Ioannis P.; Terpos, Evangelos; Alexopoulos, Harry; Politou, Marianna; Paraskevis, Dimitrios; Scorilas, Andreas; Kastritis, Efstathios; Andreakos, Evangelos; Dimopoulos, Meletios A.
Abstract : Vaccination is a major tool for mitigating the coronavirus disease 2019 (COVID-19) pandemic, and mRNA vaccines are central to the ongoing vaccination campaign that is undoubtedly saving thousands of lives. However, adverse effects (AEs) following vaccination have been noted which may relate to a proinflammatory action of the lipid nanoparticles used or the delivered mRNA (i.e., the vaccine formulation), as well as to the unique nature, expression pattern, binding profile, and proinflammatory effects of the produced antigens – spike (S) protein and/or its subunits/peptide fragments – in human tissues or organs. Current knowledge on this topic originates mostly from cell-based assays or from model organisms; further research on the cellular/molecular basis of the mRNA vaccine-induced AEs will therefore promise safety, maintain trust, and direct health policies. Highlights: Coronavirus disease 2019 (COVID-19) mRNA vaccines induce robust immune responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), yet their cellular/molecular mode of action and the etiology of the induced adverse events (AEs) remain elusive. Lipid nanoparticles (LNPs) probably have a broad distribution in human tissues/organs; they may also (along with the packaged mRNA) exert a proinflammatory action. COVID-19 mRNA vaccines encode a transmembrane SARS-CoV-2 spike (S) protein; however, shedding of the antigen and/or related peptide fragments into the circulation may occur. Binding of circulating S protein to angiotensin-converting enzyme 2 (ACE2) (that is critical for the renin–angiotensin system balance) or to other targets, along with the possibility of molecular mimicry with human proteins, may contribute to the vaccination-related AEs. The benefit–risk profile remains in favor of COVID-19 vaccination, yet prospective pharmacovigilance and long-term monitoring of vaccinated recipients should be a public health priority.